Nanosilica size-dependent toxicity in Ceriodaphnia reticulata (Cladocera) - Andrade, Victoria Soledad (2023)
Silica nanoparticles (SiNP) are the most produced nanomaterials due to their variety of applications. When released to environments, surface water bodies are their main final sink. SiNP toxicity is still inconclusive and may vary according to particle properties such as their size. We analyzed the size-related effects of SiNP (22 and 244 nm) on mortality, life history traits, and oxidative stress in the cladoceran Ceriodaphnia reticulata. The smaller SiNP (LC5072 h: 105.5 µg/ml) were more lethal than the larger ones (LC5072 h >500 µg/ml). The 22 nm-sized SiNP decreased the number of molts and neonates, increased superoxide dismutase and inhibited glutathione S-transferase activities, while larger SiNP did not exert substantial effects on the organisms at the tested concentrations. In conclusion, SiNP toxicity depended on their size, and this information should be considered for regulatory purposes and to the development of safe-by-design nanoproducts to ultimately guarantee the environment protection.